Integration of Facilities Management Considerations in Design Stage of Construction Project - Wei Hen, Neng; Sarpin, Norliana; Omar, Roshartini; Ta Wee, Seow; Kai Chen, Goh (Research in Management of Technology and Business, 2021)
Ineffective design of a facilities is one of the factors that challenge the execution of activities supported by facilities management (FM). Designers and clients are not usually interested in FM service considerations during design stage because they think they are saving money. However, ineffective design has cause issues during the post-occupancy activities of a facilities. Without any denial, integration of FM considerations in design stage is a challenging task. Therefore, the objectives of this research are to identify the challenges of integrating FM consideration during building design stage and to suggest potential approaches to improve the integration of FM considerations in building design. The scope of this research is involves FM contractor in Selangor. Quantitative method was adopted by distributing a questionnaire survey to the FM contractor. In this research, data being collected was analyzed by using Statistical Package for Social Science (SPSS) version 22.0. The results show that the most significant challenges is related to FM challenges category namely FM is still immature in Malaysia and knowledge transfer from FM to the design are still poor. The most significant potential approaches suggested is designers and clients should get the FM on board early during design stage. In conclusion, this research is important as one of the steps to improve the integration of FM considerations in design stage of a construction project.